Nanoprobe Diffusion in Poly(Vinyl-alcohol) Gels and Solutions: Effects of pH and Dehydration. Issue 1622 (2014) - Boukari, Hacène; Silva, Candida; Nossal, Ralph; Horkay, Ferenc
ABSTRACT: We report fluorescence correlation spectroscopy (FCS) measurements of the translational diffusion of two fluorescent nanoprobes, rhodamine (R6G) and carboxytetramethylrhodamine (TAMRA), embedded in poly(vinyl alcohol) (PVA) solutions and gels. The diffusion coefficient was measured as a function of the PVA concentration and pH. Furthermore, we designed and built an optical chamber to determine the diffusion coefficient of the nanoprobes within the PVA solutions and gels subjected to controlled dehydration. We find that 1) lowering pH causes an apparent slowing down of the diffusion of the nanoprobes, 2) increase of PVA concentration and crosslink density also induce slowing down of both nanoprobes, and 3) dehydration induces systematic decrease of the diffusion of TAMRA in both solutions and gels. Taken together, these results demonstrate that transient physical interactions between the nanoprobes and the PVA linear polymers have a significant effect upon nanoprobe diffusion.